Profiling of the gut, skin and nasal microbiotas revealed clinically relevant microbial taxa from children with allergies: a pilot study - Hong, Jiayi; Tang, Zhiwei; Zhang, Dongjun; Mo, Chenqi; Su, Wen; Shao, Jie (Frontiers in Allergy, 2025)
BackgroundA reduction in biodiversity and alterations in the microbiota composition are relevant to allergic diseases. However, combined analyses of the skin, nasal and gut microbiotas are lacking in the literature. In addition, in previous studies, microbiota were detected mainly by V3–V4 sequencing, but other sequences might be missed with this technique.MethodsIn this case–control study, we enrolled 3–12-year-old children with allergic rhinitis combined with atopic dermatitis and food allergy (AR-AD-FA group), children with allergic rhinitis only (AR-only) and healthy controls (HC group). We employed full-length 16S rRNA gene amplification and sequencing for the detection of gut, nasal and skin microbiota.ResultsSamples with an average sequence length of 1,459 bp were obtained in this study. Significant differences in beta diversity in the three compartments were found between the disease groups and the HC group. Differentially expressed genera were present mainly in the gut compartment. Peptoniphilus, Prevotella and Anaerococcus were abundant in the gut in the disease groups. Specifically, Streptomyces, Thermus and Pseudomonas showed differential expression in both the nasal and skin compartments of children in the disease groups.ConclusionSome meaningful differences in the abundance of some microbiota from the three compartments were observed between the disease groups and the HC group. These findings could provide new insights into the prevention and treatment of allergic diseases through the regulation of specific microbiota in the future.